Laura Jiga Iliescu. 2020. Biserica de alături. Câteva rituri necercetate ale ciobanilor din Carpați. Studiu de etnologie asupra religiozității pastorale [The church next door. Unresearched rites of the Carpathian shepherds. Ethnological study of pastoral religiosity]. Iași: Institutul European, 226 p. - Cornelia Florea (Martor)
The book Biserica de alături [The church next door] addresses some of the lesser-known rites of the shepherds from the Romanian Carpathians, such as the marriage at the fir trees, the confession, the prayer at the tree, and eating tree buds at Easter. Laura Jiga Iliescu describes these rites following long-term research on the mountain plateaus and in the hearths of the pastoral villages at the foot of the mountains.